The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1051/e3sconf/201912405059
|View full text |Cite
|
Sign up to set email alerts
|

Ensuring efficient operation of electromechanical systems with frequency regulation with periodic voltage sags

Abstract: The article reflects influence of high-power electricity consumers on control elements of frequency control of electric drive. Solution of problem of eliminating influence of voltage dips on electromechanical systems by means of a modern method of reactive power compensation is presented. Graphs of power, current, voltage versus time are presented, graphs of voltage curve are analyzed in detail with proposal of method of its normalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Semiconductor elements that generate mostly «white noise» are poorly suited for the usual Fourier analysis. Its low accuracy may affect the failure of semiconductor voltage sensors that are used in systems of APM, smart home, smart city, lean manufacturing, and others [15][16][17][18]. Given that above things are being developed and placed everywhere, elimination of frequency noise and its diagnosis will be a priority in near future.…”
Section: Processing Of Results and Conclusionmentioning
confidence: 99%
“…Semiconductor elements that generate mostly «white noise» are poorly suited for the usual Fourier analysis. Its low accuracy may affect the failure of semiconductor voltage sensors that are used in systems of APM, smart home, smart city, lean manufacturing, and others [15][16][17][18]. Given that above things are being developed and placed everywhere, elimination of frequency noise and its diagnosis will be a priority in near future.…”
Section: Processing Of Results and Conclusionmentioning
confidence: 99%
“…Voltage dips are mainly caused by power line faults such as short circuits and large induction motors starting [3]. Voltage sags are the main cause of disturbances in variable speed drives, computers, and industrial process controllers [4], [5]. Research by Wagner et al [6], a case study on the monitoring of disturbances related to power quality revealed that 68% of recorded disturbances are voltage sags and that they represent the main cause of production shutdowns and losses.…”
Section: Introductionmentioning
confidence: 99%